Emerging Evidence of the Gut Microbiome in Chemotherapy: A Clinical Review - Oh, Byeongsang; Boyle, Frances; Pavlakis, Nick; Clarke, Stephen; Guminski, Alex; Eade, Thomas; Lamoury, Gillian; Carroll, Susan; Morgia, Marita; Kneebone, Andrew; Hruby, George; Stevens, Mark; et al. (Frontiers in Oncology, 2021)
Increasing evidence suggests that the gut microbiome is associated with both cancer chemotherapy (CTX) outcomes and adverse events (AEs). This review examines the relationship between the gut microbiome and CTX as well as the impact of CTX on the gut microbiome. A literature search was conducted in electronic databases Medline, PubMed and ScienceDirect, with searches for “cancer” and “chemotherapy” and “microbiome/ microbiota”. The relevant literature was selected for use in this article. Seventeen studies were selected on participants with colorectal cancer (CRC; n=5), Acute Myeloid Leukemia (AML; n=3), Non-Hodgkin’s lymphoma (n=2), breast cancer (BCa; n=1), lung cancer (n=1), ovarian cancer (n=1), liver cancer (n=1), and various other types of cancers (n=3). Seven studies assessed the relationship between the gut microbiome and CTX with faecal samples collected prior to (n=3) and following CTX (n=4) showing that the gut microbiome is associated with both CTX efficacy and toxicity. Ten other prospective studies assessed the impact of CTX during treatment and found that CTX modulates the gut microbiome of people with cancer and that dysbiosis induced by the CTX is related to AEs. CTX adversely impacts the gut microbiome, inducing dysbiosis and is associated with CTX outcomes and AEs. Current evidence provides insights into the gut microbiome for clinicians, cancer survivors and the general public. More research is required to better understand and modify the impact of CTX on the gut microbiome.